Eksplorasi Peran Dukungan Keluarga, Pengetahuan Kewirausahaan dan Akses Kredit Terhadap Pengalaman Memulai Usaha - Negara, Rameez Ali Surya; Putra, Andro Rohmana; Panji, Dwi (CV. Lenggogeni Data Publishing, 2025)
This study aims to explore the role of family support, entrepreneurial knowledge, and access to credit in shaping individuals' experiences when starting a business. Using a qualitative approach through in-depth interviews with entrepreneurs from diverse age groups and professions, the findings reveal that family support plays a crucial role, not only emotionally but also practically in daily operations and initial capital. Entrepreneurial knowledge obtained from formal education, training programs, and business communities equips entrepreneurs with the ability to face early challenges and make strategic decisions. Meanwhile, access to credit—whether from formal financial institutions or informal sources—significantly influences business growth, despite often being constrained by administrative requirements. These three factors interact and form a foundational pillar in the early phase of entrepreneurship. The findings contribute to a deeper understanding of the early dynamics of business formation and highlight the importance of a holistic approach in supporting emerging entrepreneurs in Indonesia.